Diatoms associated with seaweeds from Moen Island in Chuuk Lagoon, Micronesia - Park, Joon Sang; Lobban, Christopher S.; Lee, Kyun-Woo (Phytotaxa, 2018)
In order to contribute understanding of the biodiversity of seaweed-associated diatoms at Moen Island in Chuuk lagoon, Micronesia in the tropical western Pacific, we collected four macroalgae (Halimeda sp., Padina sp., Sargassum sp., Dictyota sp.) that were distributed throughout at 5 subtidal sites of reef flat. These are the first records of diatoms from Chuuk, Federated States of Micronesia. A total 148 taxa belonging to 30 families and 49 genera were briefly documented with the identification references, dimension and illustrations, but many taxa could only be identified to genus. There is much similarity to the flora of Guam, but 16 records are new for the region. Four nomenclatural changes were necessary in consequence of the findings of Ruck et al. (2016) on Surirellales and Rhopalodiales.